Cover Image. (13th November 2018) - Sepulveda‐Jauregui, Armando; Martinez‐Cruz, Karla; Lau, Maximilian; Casper, Peter
Abstract : The cover image is based on the Standard Paper Assessment of methane and carbon dioxide emissions in two sub‐basins of a small acidic bog lake artificially divided 30 years ago by Armando Sepulveda‐Jauregui et al., DOI:10.1111/fwb.13182 . Photo credit: W. Scheffler.